2016
DOI: 10.1158/1078-0432.ccr-15-2314
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Next-Generation Sequencing into Routine Clinical Care to Direct Treatment of Head and Neck Squamous Cell Carcinoma

Abstract: Purpose: The clinical impact of next-generation sequencing (NGS) in patients with head and neck squamous cell carcinoma (HNSCC) has not been described. We aimed to evaluate the clinical impact of NGS in the routine care of patients with HNSCC and to correlate genomic alterations with clinical outcomes.Experimental Design: Single-center study examining targeted NGS platform used to sequence tumor DNA obtained from 213 HNSCC patients evaluated in outpatient head and neck oncology clinic between August 2011 and D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 32 publications
1
42
2
Order By: Relevance
“…We did, however, note that mutations in genes known to activate PI3K signalling were non-statistically enriched in recurrent/metastatic cases and found that there was an association between PI3K activating events and poor outcome among recurrent and metastatic NPC patients (Supplementary Fig. 14), in accordance with data presented in HNSCC24. This finding could have therapeutic implications in that targeted kinase inhibitors are often explored initially in the recurrent/metastatic setting.…”
Section: Resultssupporting
confidence: 84%
“…We did, however, note that mutations in genes known to activate PI3K signalling were non-statistically enriched in recurrent/metastatic cases and found that there was an association between PI3K activating events and poor outcome among recurrent and metastatic NPC patients (Supplementary Fig. 14), in accordance with data presented in HNSCC24. This finding could have therapeutic implications in that targeted kinase inhibitors are often explored initially in the recurrent/metastatic setting.…”
Section: Resultssupporting
confidence: 84%
“…In 7 patients (13%), NGS nominated targeted therapies, similar to the rate in another recent HNSCC precision oncology study (10%). 21 Four patients with alterations in PIK3CA or PTEN were treated on PI3K inhibitor trials, 1 HRAS mutation on a farnesyl transferase inhibitor trial, 1 MAPK1 mutation with an ERK inhibitor on a single-patient IND (Investigational New Drug) application, and 1 SMARCB1 deletion on an EZH2 inhibitor trial. In 6 patients (12%), the lack of actionable alterations on MSK-IMPACT prompted the decision to instead enroll on immunotherapy trials.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this initiative has enabled a large number of other more focused studies of common and uncommon tumor types and, in particular, has permitted prospective identification of relatively uncommon genomic variants to facilitate clinical trial enrollment and biomarker studies (46)(47)(48)(49)(50)(51)(52)(53)(54). Migrating to a clinical test, identifying when in the course of a patient's disease genomic profiling should be used, and triaging patients in real-time for clinical trial enrollment should contribute to determining clinical utility on a broader scale.…”
Section: Discussionmentioning
confidence: 99%